2015
DOI: 10.1111/cag.12172
|View full text |Cite
|
Sign up to set email alerts
|

La fluidité de l'espace montréalais : étude sur la diffusion de la diversité ethnoculturelle à Montréal entre 2001 et 2006

Abstract: The recent increase in ethno‐cultural diversity has raised numerous questions in countries of immigration. One of them focuses on the processes and mechanisms that lead to the creation of integrated or multiethnic neighbourhoods. To address it, various models were elaborated to explain the phenomenon. We will first recall the main features of these various models. Afterward, we test the hypothesis proposed by Germain and Poirier to explain the evolution of ethno‐cultural diversity in Montreal. This hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Independent of the gentrification problem, a number of research projects have looked at dynamics related to socio-ethnic transformations in Montreal's neighbourhoods. These studies showed that immigrants are more evenly dispersed throughout the city and its suburbs than were immigrants of previous generations (Germain and Poirier, 2007;Leloup, 2015). While the distribution of ethno-cultural groups in the Montreal area has never given rise to ghettos or high levels of segregation (Apparicio and al., 2006), most neighbourhoods have become multi-ethnic in character and generally more cosmopolitan (Germain and Poirier, 2007;Radice, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Independent of the gentrification problem, a number of research projects have looked at dynamics related to socio-ethnic transformations in Montreal's neighbourhoods. These studies showed that immigrants are more evenly dispersed throughout the city and its suburbs than were immigrants of previous generations (Germain and Poirier, 2007;Leloup, 2015). While the distribution of ethno-cultural groups in the Montreal area has never given rise to ghettos or high levels of segregation (Apparicio and al., 2006), most neighbourhoods have become multi-ethnic in character and generally more cosmopolitan (Germain and Poirier, 2007;Radice, 2016).…”
Section: Introductionmentioning
confidence: 99%